Logistics and supply chain management: the importance of integration for business processes / Izwan Azmi … [et al.] - Azmi, Izwan; Abdul Hamid, Norlida; Md Hussin, Md Nasarudin; Ibtishamiah, Nik (Universiti Teknologi MARA Selangor, 2017)
This conceptual paper outlines the importance of integration in supply chain management (SCM) by linking the functions of logistics as it applies in strategic business process. Often, business processes are developed at the strategic level but are never identified precisely in logistics or in SCM. Strategic business processes like Customer Relationship Management (CRM), Supplier Relationship Management (SRM), Customer Service Management (CSM) and Demand Management are not directly linked to logistics or SCM. This paper identifies the literature that expressed the importance of integration and how business processes can be relevant in the execution of key logistics activities in the supply chain context.